Développer puis réduire les expressions suivantes.
A = 3(x-2)
B = -4(2x + 1)
C = -5x (-x + 2)
D = (3x - 2)²
E = (4x + 1)²
F = ( x + 3)( x - 1)
G = (2x - 1)(2x + 1)
H = (3x - 5)(-2x + 1)
I = 3(x - 2)( x + 5)
K = -2(x + 3)(2x-4)
L = 4(x - 3)²
M = ( x + 1)²-( 2x + 3)( x - 5)

2

Réponses

2014-08-27T16:30:21+02:00
Bonjour

A = 3(x-2)
A = 3x - 6

B = -4(2x + 1)
B = -8x - 4

C = -5x (-x + 2)
C = 10x² - 10x

D = (3x - 2)²
D = 9x² - 12x + 4

E = (4x + 1)²
E = 16x² + 8x + 1

F = ( x + 3)( x - 1)
F = x² - x + 3x - 3
F = x² + 2x - 3

G = (2x - 1)(2x + 1)
G = 4x² + 2x - 2x - 1
G = 4x² - 1

H = (3x - 5)(-2x + 1)
H = -6x² + 3x + 10x - 5
H = -6x² + 13x - 5

I = 3(x - 2)( x + 5)
I = 3(x² + 5x - 2x - 10)
I = 3(x² + 3x - 10)
I = 3x² + 9x - 30

K = -2(x + 3)(2x-4)
K = -2(2x² - 4x + 6x - 12)
K = -2(2x² + 2x - 12)
K = -4x² - 4x + 22

L = 4(x - 3)²
L = 4(x² - 6x + 9)
L = 4x² - 24x + 36

M = ( x + 1)²-( 2x + 3)( x - 5)

M = (x² + 2x + 1) - (2x² - 10x + 3x - 15)
M = x² + 2x + 1 - 2x² + 10x - 3x + 15
M = x² - 2x² + 2x + 10x - 3x + 1 + 15
M = -x² + 9x + 16
2014-08-27T16:44:45+02:00
Développer puis réduire les expressions suivantes :

A = 3(x - 2)
A = 3x - 6

B = -4(2x + 1)
B = - 8x - 4

C = -5x (-x + 2)
C = 5x² - 10x

D = (3x - 2)²
D = (3x - 2) (3x - 2)
D = 9x² - 6x - 6x + 4
D = 9x² - 12x + 4

E = (4x + 1)²
E = (4x + 1) (4x + 1)
E = 16x² + 4x + 4x + 1
E = 16x² + 8x + 1

F = ( x + 3)( x - 1)
F = x² - x + 3x - 3
F = x² + 2x - 3

G = (2x - 1)(2x + 1)
G = 4x² + 2x - 2x - 1
G = 4x² - 1

H = (3x - 5)(-2x + 1)
H = -6x² + 3x + 10x - 5
H = - 6x² + 13x - 5

I = 3(x - 2)( x + 5)
I = 3 (x² + 5x - 2x - 10)
I = 3x² + 15x - 6x - 30
I = 3x² + 9x - 30

K = -2(x + 3)(2x - 4)
K = - 2 (2x² - 4x + 6x - 12)
K = 4x² + 8x - 12x + 24
K = 4x² - 4x + 24

L = 4(x - 3)²
L = 4 (x - 3) (x - 3)
L = 4 (x² - 3x - 3x + 9)
L = 4x² - 12x - 12x + 36
L = 4x² - 24x + 36

M = ( x + 1)²-( 2x + 3)( x - 5)

M = (x + 1) (x + 1) - (2x + 3) (x - 5)
M = (x² + x + x + 1) - (2x² - 10x + 3x - 15)
M = x² + 2x + 1 -  2x² + 10x - 3x + 15
M = - x² + 9x + 16